Impact of Green HRM Practices on Job Performance of Faculties with Special Reference to Select Higher Educational Institutions, Tamil Nadu - Musthaq, I.A.Ahamed Wasim; Jegadeeshwaran, M. (PT FORMOSA CENDEKIA GLOBAL, 2023)
Green HRM practices are considered the most important aspect of every organization. The study aims to identify the perception of faculties and the impact of Green HRM practices on the job performance of faculties in select higher educational institutions. Teaching faculties are the backbone of higher educational institutions. So, the well-being of the faculties is essential for the success of an institution. The study adopted a descriptive research method and a Simple random sampling technique. Samples consist of 200 teaching faculties in five colleges ranked by the National Assessment and Accreditation Council (NAAC) and the National Institutional Ranking Framework (NIRF) in Tamil Nadu and the collected data is analyzed using various statistical tools such as Exploratory factor analysis, ANOVA, correlation and multiple regressions. Hence, better green HRM practices are essential for every institution which contributes towards job involvement, job attachment, and job commitment. This paper tries to prove the relationship between various Green HRM practices with the Job performance of teaching faculties in select higher educational institutions in Tamil Nadu